Chemical synthesis of the ubiquitinated form of histone H3 and its effect on DNA methyltransferase 1. (15th July 2019) - Kawakami, Toru; Mishima, Yuichi; Takazawa, Masaya; Hojo, Hironobu; Suetake, Isao
Abstract : Posttranslational modifications of histone proteins, which form nucleosome cores, play an important role in gene regulation. Ubiquitination is one such modification. We previously reported on the synthesis of ubiquitinated histone H3 with an isopeptide mimetic structure. In this report, we describe the preparation of ubiquitinated histone H3 peptides with a native isopeptide structure, which showed a slightly weaker effect on the enzymatic activity of DNA methyltransferase 1 than the previous ubiquitinated H3 peptide analogs. These findings show that a native structure is important for determining the mechanism of the function, although ubiquitinated H3 peptide analogs can mimic the role of the original ubiquitinated H3. We also report on the successful preparation of the ubiquitinated full length histone H3. Abstract : Histone H3 ubiquitinated at the 18 position was prepared by CPE ligation. The native structure of the isopeptide is important for its function as demonstrated by the ubiquitinated H3 peptide.